One night at the Caribbean Campsite / Raja Rosila Raja Berahim - Raja Berahim, Raja Rosila; Ab Latif, Nur Afiqah (Academy of Language Studies, 2024)
Camping has become a popular activity among Malaysians today. Many people share videos on social media, showing their camping adventures, and new campsites are being set up all over the country. After long work hours and dealing with stress, being close to nature with its green scenery, fresh peacefulness can make people feel healed and refreshed. Over a weekend last year, my friend Afiqah, her family, my sister, and I planned a camping trip to Caribbean Campsite, which is located beach in Ruat village, Yan, Kedah. We on the booked two camping spots for M- sized tents at RM30 each, a great deal considering the stunning views. The campsite’s front faces the sea, while coconut trees swaying in the breeze while the back offers a picturesque air, gentle wind, rain, and view of paddy fields and Jerai Hill.